DAMAGE OF ROOT ROT DISEASE OF WHEAT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article provides information about the harmfulness of wheat root rot. Based on research, the importance of the role of precursors in reducing the incidence of root rot is shown. This information is important for protecting wheat from diseases during the growing season and growing a high-quality crop against them.